Screening for Alzheimer's disease in low-educated or illiterate older adults in Brazil: a systematic review - Luciane de Fátima Viola Ortega; Ivan Aprahamian; Marcus Kiiti Borges; João de Castilho Cação; Mônica Sanches Yassuda (Arquivos de Neuro-Psiquiatria)
ABSTRACT Cognitive screening instruments are influenced by education and/or culture. In Brazil, as illiteracy and low education rates are high, it is necessary to identify the screening tools with the highest diagnostic accuracy for Alzheimer's disease (AD). Objective: To identify the cognitive screening instruments applied in the Brazilian population with greater accuracy, to detect AD in individuals with a low educational level or who are illiterate. Methods: Systematic search in SciELO, PubMed and LILACS databases of studies that used cognitive screening tests to detect AD in older Brazilian adults with low or no education. Results: We found 328 articles and nine met the inclusion criteria. The identified instruments showed adequate or high diagnostic accuracy. Conclusion: For valid cognitive screening it is important to consider sociocultural and educational factors in the interpretation of results. The construction of specific instruments for the low educated or illiterate elderly should better reflect the difficulties of the Brazilian elderly in different regions of the country.